(3eUMa TQjas ((3jGbhJ GdeSJYUei s)
(3ChdgG (B:s
(3ShQI GdaGJMI GdMeO ddg QH GdYGdejf GdQMef GdQMje eGdc jhe GdOjf s
(3BNQgG (B:s
(3ShQI GdeYGQL jhe jNQLhf ef GdCLOGK hPdc Gdjhe GdPi cGfhG jhYOhf s
(3bWYI efg jTJed Ydi ShQI GdaGJMg LRA ef ShQI GdHbQI hShQI Gdcgas
(3ecJhH YdjgG HGdCdhGf GdCRQb hGdCMeQ hCRQb ZGeb hCNVQ aGJMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3GdcJH GdSeGhjIs